Chronic Constipation: Current Treatment Options - Louis Wing Cheong Liu (Canadian Journal of Gastroenterology)
Chronic constipation is a common functional gastrointestinal disorder that affects patients of all ages. In 2007, a consensus group of 10 Canadian gastroenterologists developed a set of recommendations pertaining to the management of chronic constipation and constipation-dominant irritable bowel syndrome. Since then, tegaserod has been withdrawn from the Canadian market. A new, highly selective serotonin receptor subtype 4 agonist, prucalopride, has been examined in several large, randomized, placebo-controlled trials demonstrating its efficacy and safety in the management of patients with chronic constipation. Additional studies evaluating the use of stimulant laxatives, polyethylene glycol and probiotics in the management of chronic constipation have also been published. The present review summarizes the previous recommendations and new evidence supporting different treatment modalities – namely, diet and lifestyle, bulking agents, stool softeners, osmotic and stimulant laxatives, prucalopride and probiotics in the management of chronic constipation. A brief summary of lubiprostone and linaclotide is also presented. The quality of evidence is presented by adopting the Grading of Recommendations, Assessment, Development and Evaluation system. Finally, a management pyramid for patients with chronic constipation is proposed based on the quality of evidence, impact of each modality on constipation and on general health, and their availabilities in Canada.